Oversized three-dimensional ordered macroporous multi-metal prussian blue analogue as well as preparation method and application thereof

Polystyrene colloidal ball templates were prepared by emulsion polymerization, and combined with aqueous solution infiltration and vacuum degassing technology, ultra-large-sized three-dimensional orderly large-pore polymetallic Prussian blue analogs were successfully prepared, solving the problem of excessive micropores of existing materials, achieving significant improvement in material performance and optimization of electrochemical performance.

CN119503837APending Publication Date: 2025-02-25YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411686071.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The micropores of existing Prussian blue analog materials are too small, limiting their performance in catalysis, separation and energy applications.

Method used

The polystyrene colloidal ball template was prepared by emulsion polymerization method, and the precursor filling and generation of Prussian blue analog was achieved through aqueous solution infiltration and vacuum degassing environment. Finally, the template was removed by solution soaking and washing to obtain an ultra-large-size three-dimensional ordered macroporous polymetallic Prussian blue analog.

Benefits of technology

The obtained material has a three-dimensional ordered structure with uniform large pore size and uniform distribution, which can fully expose active sites, improve ion/electron diffusion kinetics, and adjustable metal components to achieve excellent electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503837A_ABST
    Figure CN119503837A_ABST
Patent Text Reader

Abstract

The invention relates to an oversized three-dimensional ordered macroporous multi-metal Prussian blue analogue and a preparation method and application thereof, and the preparation method comprises the following steps: preparing polystyrene colloidal spheres by using styrene as a monomer, water as a solvent, potassium persulfate as an initiator and polyvinylpyrrolidone as a surfactant by using an emulsion polymerization method; then centrifuging to obtain a self-assembled three-dimensional ordered polystyrene colloidal sphere template; filling of the precursor of the Prussian blue analogue in gaps of the polystyrene colloidal sphere template is realized in a vacuum degassing environment through an aqueous solution infiltration method; aging in a vacuum degassing environment to realize generation of the Prussian blue analogue in gaps of the polystyrene colloidal sphere template; the polystyrene colloidal spheres are soaked and washed with an N, N-dimethylformamide solution, so that the polystyrene colloidal spheres are dissolved, and the polystyrene colloidal sphere template is removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of Prussian blue analogs, and specifically relates to an ultra-large-size three-dimensional ordered macroporous multi-metal Prussian blue analog, and a preparation method and application thereof. Background Art

[0002] Porous materials are of great significance in various applications such as catalysis, separation, and energy. In particular, crystalline porous materials, including zeolites, metal-organic frameworks (MOFs), and covalent organic frameworks (COFs), have attracted more attention due to their uniform pore size and ordered pore distribution, which often lead to improved performance. Unfortunately, the pore sizes of these materials are usually concentrated in the microporous range (<2 nm), which poses a great obstacle to their diffusion applications. Introducing macropores or mesopores to fabricate hierarchically ordered macro / meso-microporous structures is an effective way to achieve efficient mass transfer and generate fully exposed active surfaces in the porous framework. At the same time, endowing hierarchically ordered macro / mesoporous frameworks with long-range crystalline ordered properties is highly desirable in terms of overall structural stability, but it remains a daunting challenge. High-quality ordered macroporous materials are mainly synthesized by hard template methods. To date, the controllable growth of crystalline porous materials in three-dimensional ordered superpolymer templates is considered to be the most effective way to prepare targeted macro- and microporous materials.

[0003] The molecular formula of Prussian blue (PB) and its analogs (PBAs) is A x M y [M'(CN)6] z ·nH2O(A=Na + or K + ,M / M'=Fe 2+ ,Co 2+ , Ni 2+ , Mn 2+ etc.) have been widely studied for applications in catalysts, sensors, and energy storage / conversion due to their diverse compositions, open zeolite-like frameworks, diverse morphologies, and structures. Due to their chemical stability, PB and PBAs can be used as versatile precursors / templates to synthesize various functional composites with hollow or porous structures. Constructing interconnected and highly ordered macroporous structures in PB / PBAs is an unprecedented approach that can fully expose additional reaction sites and facilitate ion / electron diffusion kinetics. At the same time, synthesizing PB / PBAs with interconnected and highly ordered macroporous structures is an attractive but challenging task, considering the importance of developing a general synthetic method for such structures. Summary of the invention

[0004] Technical problem to be solved: In view of the fact that the micropores of existing Prussian blue analogue materials are too small, the present invention provides an ultra-large-sized three-dimensional ordered macroporous multi-metal Prussian blue analogue and its preparation method and application

[0005] Technical solution: A method for preparing an ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue, comprising the following steps: (1) using an emulsion polymerization method, with styrene as a monomer, water as a solvent, potassium persulfate as an initiator, and polyvinyl pyrrolidone as a surfactant, to prepare polystyrene colloidal spheres at 70-95°C, and then using centrifugation to obtain a self-assembled three-dimensional ordered polystyrene colloidal sphere template; (2) using an aqueous solution infiltration method to fill the gaps of the polystyrene colloidal sphere template with a precursor of a Prussian blue analogue in a vacuum degassed environment; (3) aging in a vacuum degassed environment to generate a Prussian blue analogue in the gaps of the polystyrene colloidal sphere template; and (4) dissolving the polystyrene colloidal sphere by immersion washing in an N,N-dimethylformamide solution to remove the polystyrene colloidal sphere template.

[0006] The specific method of step (1) is as follows: according to the proportion, 20-35 mL of styrene and 0.5-2 g of polyvinyl pyrrolidone (PVP) are added to 150-200 mL of water, and nitrogen is introduced, and stirred for 0.5-1 h, then the temperature is raised to 70-95° C., potassium persulfate with a mass fraction of 0.1-0.2 wt % is added, and stirring is maintained for 12-36 h. The precipitate obtained after centrifugal washing is dried for 12-24 h, and finally a three-dimensional ordered polystyrene colloidal sphere template is obtained.

[0007] The specific method of step (2) is to immerse 0.8-1.2g of the three-dimensional ordered polystyrene colloidal sphere template in 25-30mL of a precursor solution with a concentration of 0.06-0.08mol / L according to proportion, and then vacuum degas in a vacuum drying oven to allow the solution to completely enter the gaps of the three-dimensional ordered polystyrene colloidal sphere template, take out the fully infiltrated three-dimensional ordered polystyrene colloidal sphere template, and dry it in an oven.

[0008] The precursor is at least one of potassium ferrocyanide, potassium ferrocyanide and potassium cobalt cyanide.

[0009] The specific method of step (3) is to immerse 0.8-1.2g of the dried three-dimensional ordered polystyrene colloidal sphere template in 25-30mL of a metal salt solution with a concentration of 0.06-0.08mol / L according to proportion, and then vacuum degas in a vacuum drying oven to ensure that the metal salt and the precursor are generated in the gaps of the three-dimensional ordered polystyrene colloidal sphere template, and then age at room temperature and freeze-dry.

[0010] The metal salt is at least one of cobalt chloride, nickel chloride, iron chloride, zinc chloride, manganese chloride, copper chloride and vanadium chloride.

[0011] The specific method of step (4) is to transfer the dried three-dimensional ordered polystyrene colloidal sphere template to an N,N-dimethylformamide solution, soak it and then wash it with an N,N-dimethylformamide solution to remove the template, and finally wash it with water and ethanol, freeze-dry it, and finally obtain an ultra-large-sized three-dimensional ordered macroporous multi-metal Prussian blue analogue.

[0012] The ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue prepared by the above method.

[0013] Application of the above-mentioned ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue in the preparation of batteries.

[0014] Beneficial effects: As described above, the present invention aims to provide an ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue and its preparation method and application, using a template method based on a polystyrene colloidal sphere template. Compared with the traditional method for preparing catalysts, the steps are simple, and the obtained catalyst is a Prussian blue analogue material with three-dimensional ordered macropores, and the macropores have uniform pore size and uniform distribution. Compared with traditional Prussian blue analogues, it has convenient mass transfer channels, can fully expose active sites, has strong periodicity of pore structure arrangement, narrow pore size distribution, and uniform and adjustable macropore size. Combined with flexible and adjustable metal components, excellent electrochemical performance can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a scanning electron microscope image of the three-dimensional ordered macroporous NiFePBA obtained in Example 1.

[0016] Figure 2 This is a transmission electron microscopy image of the three-dimensional ordered macroporous NiFePBA obtained in Example 1.

[0017] Figure 3 This is the X-ray diffraction pattern of the three-dimensional ordered macroporous NiFePBA obtained in Example 1.

[0018] Figure 4 This is a surface scanning spectrum of element distribution of the three-dimensional ordered macroporous NiFePBA obtained in Example 1.

[0019] Figure 5 This is a scanning electron microscope image of the three-dimensional ordered macroporous NiMnVFePBA obtained in Example 2.

[0020] Figure 6 This is a transmission electron microscopy image of the three-dimensional ordered macroporous NiMnVFePBA obtained in Example 2.

[0021] Figure 7 This is the X-ray diffraction pattern of the three-dimensional ordered macroporous NiMnVFePBA obtained in Example 2.

[0022] Figure 8 This is a surface scanning spectrum of element distribution of the three-dimensional ordered macroporous NiMnVFePBA obtained in Example 2.

[0023] Fig. 9 This is a scanning electron microscope image of the three-dimensional ordered macroporous NiCoMnCuFePBA obtained in Example 3.

[0024] Fig.10 This is a transmission electron microscope image of the three-dimensional ordered macroporous NiCoMnCuFePBA obtained in Example 3.

[0025] Fig.11 This is the X-ray diffraction pattern of the three-dimensional ordered macroporous NiCoMnCuFePBA obtained in Example 3.

[0026] Fig.12 This is a surface scanning spectrum of element distribution of the three-dimensional ordered macroporous NiCoMnCuFePBA obtained in Example 3.

[0027] Fig.13 This is a polarization curve spectrum of the oxygen evolution reaction of the material obtained in Example 1-3 in 1.0 mol / L KOH solution. DETAILED DESCRIPTION

[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0029] It should be noted that the process equipment or devices not specifically specified in the following embodiments are all conventional equipment or devices in the art; all pressure values ​​and ranges refer to absolute pressures.

[0030] In addition, it should be understood that one or more method steps mentioned in the present invention do not exclude the existence of other method steps before or after the combination step or the insertion of other method steps between these explicitly mentioned steps, unless otherwise specified; it should also be understood that the combination connection relationship between one or more devices / apparatuses mentioned in the present invention does not exclude the existence of other devices / apparatuses before or after the combination device / apparatus or the insertion of other devices / apparatuses between these explicitly mentioned two devices / apparatuses, unless otherwise specified. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0031] Example 1

[0032] (1) Take 30 mL of styrene, wash it three times with a prepared 10% NaOH solution to remove the inhibitor, then wash it three times with deionized water to remove the NaOH, measure 26 mL of the washed styrene and 200 mL of deionized water and add them to a 250 mL three-necked flask, then add 1 g of polyvinyl pyrrolidone (PVP) and pass nitrogen for 15 minutes, transfer the three-necked flask to a 75°C oil bath, set up the device, stir magnetically for 30 minutes, dissolve 0.4 g of potassium persulfate in 20 mL of water and quickly add it to the three-necked flask to initiate the polymerization reaction, keep stirring for 24 hours, turn off the oil bath, cool for 3 hours, put the milky white liquid into a beaker and seal it for use. Take a small amount of the milky white liquid and add it to a centrifuge tube. Centrifuge it at 10000 rpm for 30 minutes, and dry the precipitate at 50°C overnight to finally obtain a 3D PS template.

[0033] (2) 0.6336 g of potassium ferrocyanide was dissolved in 25 ml of deionized water, and then a large piece of 3D PS template was immersed in the potassium ferrocyanide solution for 1 hour. The potassium ferrocyanide solution in which the PS template was immersed was then transferred to a vacuum drying oven and vacuum degassed at 30 °C for 5 hours to ensure that the solution completely entered the gaps in the 3D PS template. The fully infiltrated 3D PS template was taken out and dried in an oven at 50 °C for 12 hours.

[0034] (3) The dried 3D PS template was immersed in 0.3638 g of nickel chloride solution for 1 hour, and then the nickel chloride solution in which the 3D PS template was immersed was transferred to a vacuum drying oven and vacuum degassed at 30°C for 5 hours to ensure that the metal salt and the precursor were generated in the gaps of the 3D PS template. The template was then aged at room temperature for 12 hours, and the fully immersed 3D PS template was taken out and freeze-dried for 24 hours.

[0035] (4) The dried 3D PS template was transferred to an N,N-dimethylformamide solution and soaked for 24 h. The 3D PS template was then washed with DMF several times to completely remove the 3D PS template. Finally, the 3D PS template was washed with water and ethanol several times and freeze-dried for 24 h to obtain an ultra-large three-dimensional ordered macroporous NiFePBA.

[0036] Example 2

[0037] According to the process flow (same as Example 1), the 3D PS template soaked in potassium ferrocyanide solution was soaked in a mixed solution of 0.1213 g nickel chloride, 0.0819 g vanadium chloride and 0.099 g manganese chloride for 1 hour, and then vacuum degassed at 30°C for 5 hours, and then aged at room temperature for 24 hours. The dried 3D PS template was transferred to N,N-dimethylformamide solution, soaked for 24 hours, and then washed with DMF several times to completely remove the 3D PS template. Finally, it was washed with water and ethanol several times, and freeze-dried for 24 hours to finally obtain an ultra-large three-dimensional ordered macroporous NiMnVFePBA.

[0038] Example 3

[0039] According to the process flow (same as Example 1), the 3D PS template soaked in potassium ferrocyanide solution was soaked in a mixed solution of 0.091 g nickel chloride, 0.0892 g cobalt chloride, 0.0639 g copper chloride and 0.0477 g manganese chloride for 1 hour, and then vacuum degassed at 30°C for 5 hours, and then aged at room temperature for 24 hours. The dried 3D PS template was transferred to N, N-dimethylformamide solution, soaked for 24 hours, and then washed with DMF several times to completely remove the 3D PS template. Finally, it was washed with water and ethanol several times, and freeze-dried for 24 hours to finally obtain an ultra-large three-dimensional ordered macroporous NiCoMnCuFePBA.

[0040] Figure 1-4 , Figure 5-8 and Figure 9-12 The material characterization results of three-dimensional ordered macroporous NiFePBA, NiMnVFePBA and NiCoMnCuFePBA obtained in Examples 1, 2 and 3 are shown respectively. Figure 1 , Figure 5 and Fig. 9 This is the scanning electron microscope image of the three materials. Figure 2 , Figure 6 and Fig.10 The transmission electron microscope images of the three materials are shown in Figure 2. From the above electron microscope characterization results, it can be seen that the three materials obtained all show obvious three-dimensional ordered macroporous structures. In addition, the characterization results of the X-ray diffraction spectrum ( Figure 3 , Figure 7 and Fig.11) It can be seen that all three materials have the crystal structure of Prussian blue analogs. Characterization results of element distribution surface scanning map ( Figure 4 , Figure 8 and Fig.12 ) shows that the different metal elements corresponding to the three materials are uniformly distributed in the three-dimensional ordered macroporous structure. The above characterization results illustrate the successful synthesis of three-dimensional ordered macroporous Prussian blue analogs of different components. The three-dimensional ordered macroporous Prussian blue analogs of different components obtained in Examples 1-3 were used as catalysts for electrocatalytic oxygen evolution reaction under the same conditions. The specific application process is as follows:

[0041] The test was conducted using a CHI660 electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.). 5 mg of catalyst powder was mixed with 1 mL of ethanol and 10 μL of 5 wt% Nafion solution (Beijing Bailingwei Technology Co., Ltd.) and ultrasonicated for 30 min. 10 μL of the mixture was applied to a 5 mm diameter glassy carbon electrode as the working electrode, saturated Hg / Hg2Cl2 as the reference electrode, and a graphite rod as the counter electrode to form a three-electrode system. The electrolyte was 1.0 mol / L KOH solution. The performance test used the polarization curve test method with a scanning speed of 5 mV / s.

[0042] pass Fig.13 The results show that the three-dimensional ordered macroporous NiCoMnCuFePBA synthesized in Example 3 has the best performance, with a current density of 17.6 mA cm at 1.7 V. -2 , which is significantly higher than the three-dimensional ordered macroporous NiFePBA synthesized in Example 1 (8.2 mA cm -2 ) and the three-dimensional ordered macroporous NiMnVFePBA (10.1 mA cm) synthesized in Example 2 -2 ).

[0043] In summary, the method for preparing a three-dimensional ordered macroporous Prussian blue analogue of the present invention has an open metal skeleton and a convenient mass transfer channel, uniform distribution of metal sites, and adjustable metal composition, and has a wide range of applications in energy conversion / storage and sustainable energy regeneration.

[0044] The above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit and essence of this invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue, characterized in that the steps include: (1) Using an emulsion polymerization method, styrene is used as a monomer, water is used as a solvent, potassium persulfate is used as an initiator, and polyvinyl pyrrolidone is used as a surfactant to prepare polystyrene colloidal spheres at 70-95°C, and then a self-assembled three-dimensional ordered polystyrene colloidal sphere template is obtained by centrifugation; (2) Through an aqueous solution infiltration method, a precursor of a Prussian blue analogue is filled into the voids of the polystyrene colloidal sphere template under a vacuum degassing environment; (3) Aging is performed under a vacuum degassing environment to achieve the generation of a Prussian blue analogue in the voids of the polystyrene colloidal sphere template; (4) The polystyrene colloidal sphere is dissolved by immersion washing in an N,N-dimethylformamide solution to achieve the removal of the polystyrene colloidal sphere template.

2. The preparation method according to claim 1, characterized in that: The specific method of step (1) is as follows: according to the proportion, 20-35 mL of styrene and 0.5-2 g of polyvinyl pyrrolidone (PVP) are added to 150-200 mL of water, and nitrogen is introduced, and the mixture is stirred for 0.5-1 h, and then the temperature is raised to 70-95° C., and potassium persulfate with a mass fraction of 0.1-0.2 wt % is added, and stirring is maintained for 12-36 h. The precipitate obtained after centrifugal washing is dried for 12-24 h, and finally a three-dimensional ordered polystyrene colloidal sphere template is obtained.

3. The preparation method according to claim 1, characterized in that: The specific method of step (2) is to immerse 0.8-1.2g of the three-dimensional ordered polystyrene colloidal sphere template in 25-30mL of a precursor solution with a concentration of 0.06-0.08mol / L according to proportion, and then vacuum degas in a vacuum drying oven so that the solution completely enters the gaps of the three-dimensional ordered polystyrene colloidal sphere template, take out the fully infiltrated three-dimensional ordered polystyrene colloidal sphere template, and dry it in an oven.

4. The preparation method according to claim 3, characterized in that: The precursor is at least one of potassium ferrocyanide, potassium ferrocyanide and potassium cobalt cyanide.

5. The preparation method according to claim 1, characterized in that: The specific method of step (3) is to immerse 0.8-1.2 g of the dried three-dimensional ordered polystyrene colloidal sphere template in 25-30 mL of a metal salt solution with a concentration of 0.06-0.08 mol / L according to proportion, and then vacuum degas in a vacuum drying oven to ensure that the metal salt and the precursor are generated in the gaps of the three-dimensional ordered polystyrene colloidal sphere template, and then age at room temperature and freeze-dry.

6. The preparation method according to claim 5, characterized in that: The metal salt is at least one of cobalt chloride, nickel chloride, ferric chloride, zinc chloride, manganese chloride, copper chloride and vanadium chloride.

7. The preparation method according to claim 1, characterized in that: The specific method of step (4) is to transfer the dried three-dimensional ordered polystyrene colloidal sphere template to an N,N-dimethylformamide solution, soak it and then wash it with an N,N-dimethylformamide solution to remove the template, and finally wash it with water and ethanol, freeze-dry it, and finally obtain an ultra-large-sized three-dimensional ordered macroporous multi-metal Prussian blue analog.

8. An ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue obtained by the method described in any one of claims 1 to 7.

9. Use of the ultra-large-sized three-dimensional ordered macroporous multi-metallic Prussian blue analogue described in claim 8 in the preparation of batteries.